2007
DOI: 10.1007/s11669-007-9160-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diffusion Coefficients of Organic Compounds in Water at Different Temperatures

Abstract: Molecular (or tracer) diffusion coefficient data were obtained for 2-naphthol, benzoic acid, salicylic acid, camphor, and cinnamic acid in water at temperatures that differ significantly from ambient value. Experimental values were determined for the dissolution of 2-naphthol in water at 283 to 368 K, of benzoic acid in water at 283 to 338 K, of salicylic acid in water at 283 to 343 K, of camphor in water at 283 to 318 K, and of cinnamic acid in water at 283 to 318 K. Empirical correlations are presented for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…The overall mean diffusion coefficient and standard deviation obtained from Table 1 27,28 It can thus be concluded that the values measured in the two experiments are consistent and that the different times at which the pictures were taken did not significantly affect the calculated diffusion coefficient. Using a 2r D variation, the results also indicate that the diffusion coefficient can be estimated with a minimum accuracy of about 10%.…”
Section: Calculation Of the Diffusion Coefficientsupporting
confidence: 52%
“…The overall mean diffusion coefficient and standard deviation obtained from Table 1 27,28 It can thus be concluded that the values measured in the two experiments are consistent and that the different times at which the pictures were taken did not significantly affect the calculated diffusion coefficient. Using a 2r D variation, the results also indicate that the diffusion coefficient can be estimated with a minimum accuracy of about 10%.…”
Section: Calculation Of the Diffusion Coefficientsupporting
confidence: 52%
“…To illustrate the range of DBLs achievable by the rotating‐disk reactor, we report, in Fig. , the theoretical DBL thicknesses for O 2 (DO2 = 1.33 × 10 −9 m 2 s −1 ; Han and Bartels ), CO32 (DCO32 = 5.21 × 10 −10 m 2 s −1 ; Zeebe ), and benzoic acid (C 7 H 6 O 2 , DC7H6O2 = 6.7 × 10 −10 m 2 s −1 ; Delgado ) as a function of the rotating speed of the disk ( ω ), for a temperature of 10°C in freshwater ( ν = 1.31 × 10 −6 m 2 s −1 ).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…6 and the values presented in Ref. [34]. Figure 6 compares the experimental diffusion coefficients in water as obtained in this work with those in Eq.…”
Section: Resultsmentioning
confidence: 51%
“…[34] at different temperatures. The amount of experimental diffusion coefficients showed good agreement with diffusion coefficients reported in [32,34]. Figure 7 reveals that the diffusion coefficient of benzoic acid in γ-Al 2 O 3 -water nanofluids was increased by temperature.…”
Section: Resultsmentioning
confidence: 99%